On the targeting and redistributive efficiencies of alternative transfer instruments - Coady, David; Skoufias, Emmanuel (International Food Policy Research Institute, 2001)
The paper shows how the so-called distributional characteristic of a policy instrument can be additively decomposed into two components; one that captures the targeting efficiency of the instrument, the other its redistributive efficiency. Using these measures, the paper provides an interpretation of the commonly used leakage and undercoverage rates (and other indices based on these concepts) within standard welfare theory. An empirical application of the decomposition approach to Mexican data is presented.